Psychiatric morbidity of migrant workers in Malaysia - for iRPA study on health problems of foreign worker - Habil, Mohd Hussain (Faculty of Medicine, University of Malaya, 2002)
Malaysia has been swamped by migrant workers from nearby countries like Indonesia, Philippine and also Bangladesh since 1980's. The main pulling forces which motivated them to migrate to Malaysia are better economy, political stability and religious freedom in Malaysia. Another way of classifying migration pattern is to divide it into push and pull migration or a combination of the two. Pull migrants are those who migrate to obtain better economic opportunity while push migrants are those who try to run away from being prosecuted or due to fear of political and religious suppression. Whatever the push and the pull factors, they are bound to encounter some acculturation challenges. This will inevitably produce certain psychological sequelae. Therefore, the main aim of this study is to determine the point prevalence of psychiatric morbidity experienced by the migrant population. The psychological impact of push and pull migrations is fundamentally distinct. There were significant numbers of migrants admitted to University Hospital psychiatric units who suffered from psychological distress and para suicide. The reasons for these problems are multi-faceted. Hence, another purpose for this study was to investigate factors which make them to be at risk of developing psychiatric morbidity. The findings of this study can be used as a basis for making recommendations to the government of the rationale to include psychological assessment as one of the important components in the pre-employment selection criteria.